Future Imaginaries of Indigenous AI - Yolgörmez, Ceyda; Kite, Suzanne; Brown, Michelle Lee; Lewis, Jason Edward (Imaginations)

(untitled) (York University, 2026)
What lies in the future of AI, and who gets to define it? The paper addresses this question through “Future Imaginaries of Indigenous AI” workshops that open space for imagining relational, community-grounded technologies. Considering AI models as cultural systems, we position the workshops as interventions into AI’s cultural foundations. We invite the reader into the workshop space by interweaving our positioning alongside the imagining exercise, and provide the reasoning and structure within which our practice takes shape. We tease out the themes that are embedded in the exercise to highlight the critical and generative dimensions, and conclude with reflections.